The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1979
DOI: 10.1103/physrevlett.42.515
|View full text |Cite
|
Sign up to set email alerts
|

Range Profiles of 300- and 475-eVHe+4Ions and the Diffusivity of

Abstract: Range profiles for 300-and 475-eV 4 He + ions implanted in situ in tungsten at 60, 61, 80, 90 K were measured, directly and absolutely, employing an atom-probe field-ion microscope. A mean range (x) of 40±4 A and a parent standard deviation (a) of 20 to 36 A was obtained for 300-eV *He + ; values of x and a of 56 ±6 A and 37 to 42 A, respectively, were determined for 475-eV 4 He + . The existence of an isolated and immobile interstitial 4 He atom was established and an enthalpy change of migration of 0.24 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
1

Year Published

1979
1979
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(26 citation statements)
references
References 10 publications
(3 reference statements)
5
20
1
Order By: Relevance
“…This results is a priori in contradiction with the experimental values of the diffusion coefficients of He [8,9]. However it was shown in [10] that the strong tendency for He to bind with itself can explain this discrepancy with the experimental data, which are very probably migration energies of small He clusters rather than of isolated He atoms [10].…”
Section: Helium and Vacancy Clusteringcontrasting
confidence: 80%
See 2 more Smart Citations
“…This results is a priori in contradiction with the experimental values of the diffusion coefficients of He [8,9]. However it was shown in [10] that the strong tendency for He to bind with itself can explain this discrepancy with the experimental data, which are very probably migration energies of small He clusters rather than of isolated He atoms [10].…”
Section: Helium and Vacancy Clusteringcontrasting
confidence: 80%
“…This is in perfect agreement with the results of Soltan and coworkers [11] who, in a careful study of hydrogen, deuterium, and helium implantation at 5 K with energies from 0.25 to 3 keV into thin films of 80 -320 nm of gold and tungsten, followed by isochronally heating of the specimens up to 400 K, demonstrated that concentrations as low as 350 ppm of He suppressed He migration because of the clustering of these elements. They furthermore calculated that in the experiments of Wagner et al [8] as well as that of Amano [9], the concentration of implanted He was 5%. They thus explain why in their own experiments, He becomes mobile at temperature below 5 K, in contradiction to the previous results [8] and [9] where mobility of 3 He and 4 He was observed only above 90 K.…”
Section: Helium and Vacancy Clusteringmentioning
confidence: 98%
See 1 more Smart Citation
“…Using DFT method, Becquart and Domain 5 calculated this value to be 0.06 eV, much smaller than experiment, which ranges from 0.24 to 0.32 eV. 6,7 Xiao et al have carefully examined the possible numerical error introduced by pseudopotential method and performed all-electron calculations to make comparison, 8 exactly the same energy barrier was obtained. Since a He-He pair in W has a strong binding (0.98 eV/pair), 5 was not the migration of a single He, but rather a He pair or even a small He cluster instead.…”
Section: Introductionmentioning
confidence: 96%
“…Such a fine structure could be part of a configuration with interconnected porosity, which would provide the helium a subsequent path of least resistance to the chamber. A simple analysis based on the diffusion coefficient for He in W from Wagner and Seidman [24] indicates that for a temperature of %1000-1500 K over a time of 0.1 s (corresponding to an example repetition rate of 10), the characteristic He diffusion length in W is about 10-50 nm. Higher temperature and/or longer times would help [3].…”
Section: Consideration Of Engineered Tungsten Armormentioning
confidence: 99%